Time-limited adolescent psychodynamic psychotherapy a developmentally focussed psychotherapy for young people - Briggs, Stephen 1951- (Routledge, 2019)
Time-Limited Adolescent Psychodynamic Psychotherapy: A Developmentally Focussed Psychotherapy for Young People will be an indispensable clinician's guide to the practice of Time-Limited Adolescent Psychodynamic Psychotherapy (TAPP), providing comprehensive instruction on the theory and delivery of this distinctive model of psychotherapy. TAPP is a manualised brief psychodynamic psychotherapy of 20 sessions, for young people between, approximately, 14 and 25 years, combining psychodynamic psychotherapy with psychosocial understanding of adolescent difficulties. It places emphasis on the therapeutic engagement of young people and works with a developmental focus to effect change and growth. Divided into two parts, "Conceptual Framework" and "Practice", this book combines digestible scholarly analysis with case studies to effect a one-stop practitioner's guide to TAPP. Time-Limited Adolescent Psychodynamic Psychotherapy: A Developmentally Focussed Psychotherapy for Young People will be of immense value to clinicians working with young people, researchers engaging with evaluating TAPP and students of psychotherapy
Keywords: Psychodynamic psychotherapy for teenagers; Mental illness / Treatment; Adolescent psychotherapy